PRENATAL YOGA'S EFFECTIVENESS IN RELIEVING THIRD-TRIMESTER PREGNANCY DISCOMFORT: A SCOPING REVIEW - Rhadiyah, Putri; Heriyanti, Silvia Widyani; Nurhayati, Aisah; Nasution, Nadhiati Awlia; Herawati, Ariana; Soraya, Ayu; Fitria, Anisa; Adnani, Qorinah Estiningtyas Sakilah (Universitas Aisyah Pringsewu, 2023)
Some pregnant women may experience discomfort in the third trimester due to physiological reasons. Urination, pain in the pit of the stomach, weariness, and pain in the back and waist area are common complaints. A pregnant woman's psychology changed from anxiety and stress to a condition-conceived baby till she was terrified to confront labour. Inconvenience during pregnancy, if not well managed, can cause psychological distress in the mother. Prenatal yoga can help pregnant women who are nervous about their pregnancy overcome their pain.The goal of this review's scoping is to examine the usefulness of deep prenatal yoga in overcoming changes in physiological causes of discomfort in the third trimester of pregnancy. In the article, there is a scoping review. The PRISMA approach is used to identify published articles over the last five years (2019-2023) via ProQuest, SAGE Journal, Science Direct, and Cochrane and produce eight suitable journals. According to the findings, practising yoga during pregnancy can help moms overcome a variety of disruptions or inconveniences that can occur during the third trimester of their pregnancy. Prenatal yoga is a non-pharmacological therapy that can be administered to a pregnant mother in her third trimester to improve sleep quality, reduce anxiety, relieve back pain, and facilitate the process of labour stage II.